Problem analysis for D’xclusive Collection booking system using SWOT analysis technique / Zatu Amirah Zulkepeli - Zulkepeli, Zatu Amirah (2017)
This project is about developing an online booking system for D’xclusive Collection using SWOT Analysis. The problem arises because of using manual system for booking. Generally, owner using form to write up customer information and booking made up by customer. This can bring loss and redundancy of the data because it takes more effort to keep track of paper document and find information. Besides, manual system can lead to redundancy of the wedding date and become inconvenient for the customer to know the availability of wedding planner. The aim for this project is to develop a booking system for wedding planner and provide an accessible website to the customer. This project used waterfall model. There are four phases incorporate in this methodology that is knowledge acquisition and literature review, requirement, design and implementation. In order to get a deeper understanding on what the stakeholder want for their system, a specific technique had been used. The technique used is SWOT Analysis technique. SWOT analysis help to examine the strength, that is in what way the system excel, the weaknesses that is what aspect in the system if not addressed well can impede business future, opportunities that is what factor need to take advantage that might enhance the quality of the system and lastly the threat what external factor that could negatively affect the future. Use Case Diagram, Activity diagram, Domain Class Diagram (DCD), Sequence Diagram, Design Class Diagram, Multilayer Sequence Diagram, Package Diagram are the deliverable of the objectives. The system developed using Eclipse and MySQL as the database. For future work, testing and mobile application are much recommended for this project o give this project more complexity and can help adding extra feature to the system.